2017
DOI: 10.4238/gmr16039859
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Novel polymorphisms in bovine CD4 and LAG-3 genes associated with somatic cell counts of clinical mastitis cows

Abstract: Clinical mastitis cows normally produce clotted milk, thus the much higher somatic cells in milk are unable to be counted by routine FOSS machine. The proteins coded by CD4 and LAG-3 genes can bind to MHC class II molecules and play important roles in inflammatory diseases. The present study was designed to investigate the effects of single nucleotide polymorphisms (SNPs) in bovine CD4 and LAG-3 genes on the somatic cell counts (SCCs) of clinical mastitis Holstein cows. For the first time, we detected SCCs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 24 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…Bacteriocins produced by certain non-aureus Staphylococci (NAS) and Corynebacterium species colonizing the teat apices and teat canals may inhibit growth of major mastitis pathogens [89]. Within complex ecosystems, ecosystem diversity can increase resiliency against an influx of external species by supporting favorable interactivity [90]. The complexity of microbe to microbe communications concerning the functional properties of the mammary ecosystem are difficult to understand.…”
Section: The Milk Microbiome and The Mammary Gland Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteriocins produced by certain non-aureus Staphylococci (NAS) and Corynebacterium species colonizing the teat apices and teat canals may inhibit growth of major mastitis pathogens [89]. Within complex ecosystems, ecosystem diversity can increase resiliency against an influx of external species by supporting favorable interactivity [90]. The complexity of microbe to microbe communications concerning the functional properties of the mammary ecosystem are difficult to understand.…”
Section: The Milk Microbiome and The Mammary Gland Healthmentioning
confidence: 99%
“…A study reported the up-regulation of CXCL8 and TNF-α in E. coli induced mastitis in mammary epithelial cells [88]. In addition, the high expression of CXCL10, CCL2, CCL5 and CCL20 was noticed in bovine mammary epithelial cells in E. coli induced mastitis, which is essential for the recruitment of leucocytes [90]. The expression levels of IL-6, complement factor 3 (C3), NFKBIA and MMP9 were also elevated during mammary gland infection [90].…”
Section: Nf-κb Regulates the Immunity And Inflammatory Linked Genes D...mentioning
confidence: 99%
“…That is why, nowadays, more interest is paid to the increase in cells and cytokine levels in milk and blood, respectively, rather than just the overall SCC, which may provide an early status of udder health [ 89 ]. A study showed that inflammatory cytokines (IL-6, IL-17, and IFN-γ, TNF-α) could be used as subclinical mastitis indicators, in addition to SCSs and SCCs [ 51 , 86 , 90 ]. In addition, it is predicted that the 39645396C/T SNP changes lysine to asparagine [ 86 ].…”
Section: The Jak-stat Signaling Role In Bovine Mastitismentioning
confidence: 99%
“…It has been reported that IL-17A and IL-17F play a critical role in regulating host–pathogen interactions during the development of mastitis [ 99 ]. The SNPs in IL-17F and IL-17A have been shown to be associated with milk SCCs [ 90 ]. Moreover, IL-17 also activates IL-6 with IFN-γ and tumor necrosis factor-alpha (TNF-α) [ 100 ].…”
Section: The Jak-stat Signaling Role In Bovine Mastitismentioning
confidence: 99%
See 1 more Smart Citation